Light Through a Crucible of Tragedy: Collaborative Transformative Learning Research Yields Social Action - Kathleen P. King (Adult Education Research Conference, 2004)
As an international group of adult educators researched transformative learning experiences during and following the attacks on the World Trade Centers on 9/11/01, they developed new understandings and a social response to the tragedy. This collaborative qualitative research used narrative and dialogue to build a greater understanding of the meaning of the participants’ experiences.